Challenges and realities of elementary school teachers in the use of technology as a teaching tool in contingency times (Revista de Investigaciones Universidad del Quindío, 2021)
The development of ICT in the 21st century has been a process of dizzying changes, prompting governments to implement public policies that allow societies to insert themselves into the information and knowledge society. The objective is to describe the realities and challenges of the elementary school teacher in the use of technology as a teaching tool in contingency times, through the phenomenological qualitative research method, to understand the teacher's experience in distance education. This study is developed under the theoretical-methodological perspective of the interpretive paradigm. It is qualitative research focused on phenomenological design. It is concluded that the most significant challenge of working from home is to achieve collaboration between the parent, student and teacher.
Keywords: Teaching; distance education; online learning